9514 1404 393
Answer:
9 7/12
Step-by-step explanation:
12 is a suitable common denominator.
(7 3/4) + (1 5/6) = (7 9/12) + (1 10/12) = (7+1) +(9/12 +10/12)
= 8 + 19/12 = 9 + 7/12 . . . . . . change 19/12 to 1 7/12
= 9 7/12
_____
My calculator works with mixed numbers very nicely, as many graphing calculators do.
Answer:
![P(x)=-5x^3-40x^2-45x+90](https://tex.z-dn.net/?f=P%28x%29%3D-5x%5E3-40x%5E2-45x%2B90)
Step-by-step explanation:
<u>Equation of a Polynomial</u>
Given the roots x1, x2, and x3 of a cubic polynomial, the equation can be written as:
![P(x)=a(x-x1)(x-x2)(x-x3)](https://tex.z-dn.net/?f=P%28x%29%3Da%28x-x1%29%28x-x2%29%28x-x3%29)
Where a is the leading coefficient.
We know the three roots of the polynomial -6, -3, and 1, thus:
![P(x)=a(x+6)(x+3)(x-1)](https://tex.z-dn.net/?f=P%28x%29%3Da%28x%2B6%29%28x%2B3%29%28x-1%29)
Since the y-intercept of the polynomial is y=90 when x=0:
90=a(0+6)(0+3)(0-1)
90=a(6)(3)(-1)=-18a
Thus
a = 90/(-18) = -5
The polynomial is:
![P(x)=-5(x+6)(x+3)(x-1)](https://tex.z-dn.net/?f=P%28x%29%3D-5%28x%2B6%29%28x%2B3%29%28x-1%29)
We must write it in standard form, so we have to multiply all of the factors as follows:
![P(x)=-5(x^2+6x+3x+18)(x-1)](https://tex.z-dn.net/?f=P%28x%29%3D-5%28x%5E2%2B6x%2B3x%2B18%29%28x-1%29)
![P(x)=-5(x^2+9x+18)(x-1)](https://tex.z-dn.net/?f=P%28x%29%3D-5%28x%5E2%2B9x%2B18%29%28x-1%29)
![P(x)=-5(x^3-x^2+9x^2-9x+18x-18)](https://tex.z-dn.net/?f=P%28x%29%3D-5%28x%5E3-x%5E2%2B9x%5E2-9x%2B18x-18%29)
![P(x)=-5(x^3+8x^2+9x-18)](https://tex.z-dn.net/?f=P%28x%29%3D-5%28x%5E3%2B8x%5E2%2B9x-18%29)
![\boxed{P(x)=-5x^3-40x^2-45x+90}](https://tex.z-dn.net/?f=%5Cboxed%7BP%28x%29%3D-5x%5E3-40x%5E2-45x%2B90%7D)
Answer:
The answer is 88, trust.
Step-by-step explanation:
N= 1 a this is the answer hope i helped
- _ + _
r pr
Answer:
The answer is no
Step-by-step explanation: